Unter uns gesagt Textstruktur und Gesprächsführung in Roman Flamenca - Majorossy, Imre Gábor (Verbum – Analecta Neolatina, 2009)
This paper deals with one of the medieval Occitan novels and mainly with its dialogues. The popular love story of Flamenca and Guillem is shattered by the jealousy of Archambaut. As part of a major work, this paper shows how complex dialogues define the plot along the conflicts and lead persons to their next measures. Besides the analysis of the most famous dialogue, which was organised in the church, new aspects of other dialogues will be unveiled. The queen acts as the Bible’s serpent, the young husband as a beast, the young woman as a fairy queen, the unknown lover as a priest, etc. They all begin to talk to each other, but nobody communicates what they really mean.